The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s0103-73312015000400003
|View full text |Cite
|
Sign up to set email alerts
|

A definição de prioridade de investimento em saúde: uma análise a partir da participação dos atores na tomada de decisão

Abstract: Os problemas de saúde possuem contornos próprios e a ação governamental para a elaboração de políticas públicas de saúde pode ser construída a partir da contribuição de diversos atores para a tomada de decisão. O estudo teve como objetivo analisar o processo de tomada de decisão sobre as prioridades de investimento a partir da percepção de diversos atores. Como método, é do tipo exploratório de corte transversal, com a utilização de abordagem qualitativa para coleta e análise de dados. Foram entrevistados 18 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
12
Order By: Relevance
“…Overcoming defensive stances and constructing a joint strategy that materializes a solidarity regionalization depend on a certain minimum convergence between the main players of the health field in each state, something that is intrinsically related to the sectorial political history 28,29 .…”
Section: Theoretical Framework: the Implementation Of Policies In Fedmentioning
confidence: 99%
“…Overcoming defensive stances and constructing a joint strategy that materializes a solidarity regionalization depend on a certain minimum convergence between the main players of the health field in each state, something that is intrinsically related to the sectorial political history 28,29 .…”
Section: Theoretical Framework: the Implementation Of Policies In Fedmentioning
confidence: 99%
“…It is observed that most CEOs managed by consortia or even cooperatives were found in cities with smaller populations, and are often organized only to provide medium complexity services [18], reducing their potential to mere service providers, when they could be an instrument of reorganization of demand and supply of services with greater efficiency and less permeated by privatist interests. On the other hand, in the southern and southeastern regions, there is a common occurrence of private administration and Social Organizations in the health network, especially linked to hospital administration [19], a fact that is repeated in CEOs in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…A participação dos atores político-institucionais deve ocorrer durante todo o processo decisório, não somente no processo final de aceitação ou negação da tomada de decisão, assim, a análise da percepção desses atores sobre a sua participação efetiva nas etapas de criação e aprovação da agenda também deve ser analisada. Em um cenário de elaboração de política pública e tomada de decisão restritas a um pequeno grupo de atores, há possibilidade de baixa adesão à decisão, financiamento insuficiente ou intermitente e, consequentemente, pouco resultado em longo prazo (SANTOS ET AL., 2015).…”
Section: Quadro 2 Análise De Casosunclassified